Consciousness and the outside world: is there anyone listening?. (June 2022) - Hight, Darren; Sleigh, Jamie
Summary: Sedated patients have graded levels of consciousness and perceptual connection with the outside world. Disconnection is associated with widespread changes in the electroencephalogram, whereas full unconsciousness is linked with decreased activity specifically in the deep midline regions of the brain. These findings can be interpreted within the predictive coding model of consciousness as differences in model generation vs discrepancy detection. Anaesthetists should be cognisant that apparently unresponsive patients might still have some ongoing partially disconnected consciousness activity.